FGF8 Activates Proliferation and Migration in Mouse Post-Natal Oligodendrocyte Progenitor Cells - Cruz-Martinez, Pablo; Martinez-Ferre, Almudena; Jaramillo-Merchán, Jesus; Estirado, Alicia; Martinez, Salvador; Jones, Jonathan (PLOS ONE, 2014)
Fibroblast growth factor 8 (FGF8) is a key molecular signal that is necessary for early embryonic development of the central nervous system, quickly disappearing past this point. It is known to be one of the primary morphogenetic signals required for cell fate and survival processes in structures such as the cerebellum, telencephalic and isthmic organizers, while its absence causes severe abnormalities in the nervous system and the embryo usually dies in early stages of development. In this work, we have observed a new possible therapeutic role for this factor in demyelinating disorders, such as leukodystrophy or multiple sclerosis. In vitro, oligodendrocyte progenitor cells were cultured with differentiating medium and in the presence of FGF8. Differentiation and proliferation studies were performed by immunocytochemistry and PCR. Also, migration studies were performed in matrigel cultures, where oligodendrocyte progenitor cells were placed at a certain distance of a FGF8-soaked heparin bead. The results showed that both migration and proliferation was induced by FGF8. Furthermore, a similar effect was observed in an in vivo demyelinating mouse model, where oligodendrocyte progenitor cells were observed migrating towards the FGF8-soaked heparin beads where they were grafted. In conclusion, the results shown here demonstrate that FGF8 is a novel factor to induce oligodendrocyte progenitor cell activation, migration and proliferation in vitro, which can be extrapolated in vivo in demyelinated animal models.